Crisis Communication And Social Media: The Mayor's Strategy Of Bandar Lampung @eva_dwiana - Rojiati, Umi; Setiawati, Rini (KOMUNIKA, 2023)
This study aims to find the results of the implications of the use of social media by the Bandar Lampung City government as a crisis communication management strategy during the Covid-19 pandemic. Crisis communication efforts are carried out through the @eva_dwiana Instagram account. This research used a qualitative content analysis method with Instagram content objects @eva_dwiana from 2019 to 2020. The results showed that the Bandar Lampung City Government, through its Mayor, used social media accounts to disseminate instructions regarding the handling of COVID-19 as well as publicize the performance carried out in overcoming the crisis. Other results also have more uploads containing instructions than performance publications. It also shows that the Bandar Lampung City Government prioritizes public safety over the institution's reputation.